Brain Metal Distribution and Neuro-Inflammatory Profiles after Chronic Vanadium Administration and Withdrawal in Mice - Folarin, Oluwabusayo R.; Snyder, Amanda M.; Peters, Douglas G.; Olopade, Funmilayo; Connor, James R.; Olopade, James O. (Frontiers in Neuroanatomy, 2017)
Vanadium is a potentially toxic environmental pollutant and induces oxidative damage in biological systems including the central nervous system. Its deposition in brain tissue may be involved in the pathogenesis of certain neurological disorders which after prolonged exposure can culminate into more severe pathology. Most studies on vanadium neurotoxicity have been done after acute exposure but in reality some populations are exposed for a lifetime. This work was designed to ascertain neurodegenerative consequences of chronic vanadium administration and to investigate the progressive changes in the brain after withdrawal from vanadium treatment. A total of 85 male BALB/c mice were used for the experiment and divided into three major groups of vanadium treated (intraperitoneally (i.p) injected with 3 mg/kg body weight of sodium metavanadate and sacrificed every 3 months till 18 months); matched controls; and animals that were exposed to vanadium for three months and thereafter the metal was withdrawn. Brain tissues were obtained after animal sacrifice. Sagittal cut sections of paraffin embedded tissue (5μm) were analysed by the Laser ablation-inductively coupled plasma-mass spectrometry (LA – ICP – MS) to show the absorption and distribution of vanadium metal. Also, Heamatoxylin and Eosin (H&E) staining of brain sections, and immunohistochemistry for Microglia (Iba-1), Astrocytes (GFAP), Neurons (Neu-N) and Neu-N + Dapi double labelling immunofluorescence were observed for morphological and morphometric parameters. The LA – ICP – MS results showed progressive increase in vanadium uptake with time in different brain regions with prediction for regions like the olfactory bulb, brain stem and cerebellum. The withdrawal brains still show presence of vanadium metal in the brain slightly more than the controls. There were morphological alterations (of the layering profile, nuclear shrinkage) in the prefrontal cortex, cellular degeneration (loss of dendritic arborization) and cell death in the Hippocampal CA1 pyramidal cells and Purkinje cells of the cerebellum, including astrocytic and microglial activation in vanadium exposed brains which were all attenuated in the withdrawal group . With exposure into old age, the evident neuropathology was microgliosis, while progressive astrogliosis became more attenuated. We have shown that chronic administration of vanadium over a lifetime in mice resulted